Hafnium-based ultrahigh-temperature ceramic-based composite material and preparation method thereof

By using carbon nanotube fiber/carbon fiber bidirectional cloth to make a pointed wedge-profile preform, combined with the treatment technology of hafnium zirconium composite ceramic precursor solution, the problem of insufficient performance of ceramic-based composite materials in preparing specific shapes is solved, and the preparation of high-performance hafnium-based ultra-high temperature ceramic-based composite materials is achieved.

CN119569471APending Publication Date: 2025-03-07AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411754238.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing ceramic matrix composites have waste and fiber breakage problems in preparing specific shapes, resulting in insufficient thermal conductivity, ablation resistance and mechanical properties.

Method used

A pointed wedge-profile preform was made by a laminated suture process using carbon nanotube fiber/carbon fiber bidirectional cloth, and a pyrolyzed carbon interface layer was prepared by chemical vapor deposition method. Then, it was impregnated, cured and cracked with a hafnium zirconium composite ceramic precursor solution to form a hafnium-based ultra-high temperature ceramic matrix composite material.

Benefits of technology

The direct integrated molding of ceramic matrix composite materials is realized, which improves its ultra-high temperature and ablation resistance in extreme environments, and improves thermal conductivity and mechanical properties, solving the problem of insufficient performance of specific shape materials in traditional technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569471A_ABST
    Figure CN119569471A_ABST
Patent Text Reader

Abstract

The invention relates to a hafnium-based ultrahigh-temperature ceramic-based composite material and a preparation method thereof. The method comprises the following steps: mixing and weaving carbon nanotube fibers and PAN-based carbon fibers to obtain carbon nanotube fiber / carbon fiber bidirectional cloth; preparing the carbon nanotube fiber / carbon fiber bidirectional cloth into a sharp wedge profiling preform by adopting a lamination sewing process; preparing a pyrolytic carbon interface layer on the fiber surface of the sharp wedge profiling preform through a chemical vapor deposition method; the hafnium-zirconium composite ceramic precursor solution is used for dipping and filling internal pores of the sharp wedge profiling preform with the pyrolytic carbon interface layer, and the hafnium-based ultrahigh-temperature ceramic-based composite material is prepared through curing and cracking reaction. The carbon nanotube fiber / carbon fiber bidirectional cloth is woven to obtain a novel structure sharp wedge profiling preform, and a hafnium zirconium carbon solid solution is introduced as a ceramic matrix, so that the ablation resistance, the mechanical property and the heat conductivity of the ceramic matrix composite material are remarkably improved; the problem that a ceramic-based composite material prepared by a traditional technology is insufficient in ablation resistance and thermal conductivity is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic-based composite material preparation, and in particular relates to a hafnium-based ultra-high temperature ceramic-based composite material and a preparation method thereof. Background Art

[0002] Ceramic-based composite materials have excellent properties such as high temperature resistance, ablation resistance, light weight, high strength and high modulus, and are new thermal structural materials for the next generation. The thermal conductivity of mesophase asphalt-based carbon fibers can reach 800W / m·K, while the thermal conductivity of conventional PAN-based carbon fibers is only 20-60W / m·K. The ultra-high thermal conductivity makes the mesophase asphalt-based carbon fibers and ceramic matrix composite materials have significant advantages in heat conduction. Due to the large modulus of general mesophase asphalt-based fibers, the fiber diameter of general mesophase asphalt-based carbon fibers can generally reach 14μm, and the flexibility is relatively poor, which makes it difficult to meet large bending. As a result, the existing preforms woven with mesophase asphalt-based carbon fibers and / or PAN-based carbon fibers are usually flat preforms. However, the ceramic-based composite materials currently made using this conventional structural preform are in the shape of a flat plate. This conventional shape cannot meet the application requirements in certain specific scenarios. In order to obtain a ceramic-based composite material of a specific shape, the traditional preparation technology usually first prepares a flat ceramic-based composite material and then processes it into a specific shape. This method that requires reprocessing leads to a large waste of ceramic-based composite materials and problems such as fiber breakage and fiber discontinuity. Ultimately, the ceramic-based composite materials of a specific shape prepared by traditional technology have deficiencies in thermal conductivity, ablation resistance and / or mechanical properties.

[0003] In addition, the existing high-performance ceramic matrix is ​​usually ZrC and HfC. Compared with ZrC, HfC has a higher melting point and better ablation resistance, but its density reaches 12.7g / cm 3 This greatly limits the application scope of HfC.

[0004] Therefore, how to simultaneously achieve high thermal conductivity, lightweight, high temperature resistance and / or excellent mechanical properties of ceramic-based composites of specific shapes has become a key research issue in this technical field.

[0005] In summary, it is very necessary to provide a hafnium-based ultra-high temperature ceramic-based composite material and a preparation method thereof. Summary of the invention

[0006] In order to solve one or more technical problems existing in the prior art, the present invention provides a hafnium-based ultra-high temperature ceramic-based composite material and a preparation method thereof. The method of the present invention obtains a novel structure wedge-shaped preform by weaving carbon nanotube fiber / carbon fiber bidirectional cloth, and introduces hafnium zirconium carbon solid solution as a ceramic matrix, which significantly improves the ablation resistance, mechanical properties and thermal conductivity of the ceramic-based composite material, realizes directional and rapid heat transmission, improves the ultra-high temperature ablation resistance of the ceramic-based composite material in extreme environments, and solves the problem of insufficient ablation resistance and thermal conductivity of the ceramic-based composite material prepared by traditional technology in a specific shape.

[0007] In a first aspect, the present invention provides a method for preparing a hafnium-based ultrahigh temperature ceramic-based composite material, the method comprising the following steps:

[0008] (1) mixing carbon nanotube fibers with PAN-based carbon fibers to obtain carbon nanotube fiber / carbon fiber bidirectional fabric;

[0009] (2) using a lamination stitching process to make a carbon nanotube fiber / carbon fiber bidirectional cloth into a wedge-shaped preform;

[0010] (3) preparing a pyrolytic carbon interface layer on the fiber surface of the pointed wedge-shaped preform by chemical vapor deposition to obtain a pointed wedge-shaped preform having a pyrolytic carbon interface layer;

[0011] (4) impregnating the wedge-shaped preform having a pyrolytic carbon interface layer obtained in step (3) with a hafnium-zirconium composite ceramic precursor solution as an impregnation liquid, then curing and cracking the preform, and repeating the impregnation, curing and cracking multiple times to obtain a hafnium-based ultrahigh temperature ceramic-based composite material.

[0012] Preferably, in step (1), the thermal conductivity of the carbon nanotube fiber is 400-1000 W / (m·K), the tensile strength is 3-5 GPa, and the elongation at break is 2.5-4%; in the carbon nanotube fiber / carbon fiber bidirectional cloth, the carbon nanotube fiber and the PAN-based carbon fiber are vertically distributed; and / or the surface density of the carbon nanotube fiber / carbon fiber bidirectional cloth is 300-400 g / m 2 .

[0013] Preferably, in step (2): the lamination and stitching process is: first fold the carbon nanotube fiber / carbon fiber bidirectional cloth in a direction perpendicular to the carbon nanotube fibers, and then stack and stitch multiple pieces of the folded carbon nanotube fiber / carbon fiber bidirectional cloth to obtain a pointed wedge-shaped preform.

[0014] Preferably, the volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers in the pointed wedge-shaped preform is (1-3): (1-3); and / or the density of the pointed wedge-shaped preform is 0.6-0.9 g / cm 3.

[0015] Preferably, in step (3): the thickness of the pyrolytic carbon interface layer is 0.1-2 μm.

[0016] Preferably, in step (4): the hafnium-zirconium composite ceramic precursor solution is prepared by: evenly mixing hafnium alkoxide and zirconium alkoxide and subjecting them to coordination reaction and co-hydrolysis reaction to obtain the hafnium-zirconium composite ceramic precursor solution; and / or the molar ratio of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution is (0.1 to 99.9): (0.1 to 99.9).

[0017] Preferably, the hafnium-zirconium composite ceramic precursor solution has a solid content of 40 to 65 wt % and a viscosity of 40 to 120 mPa·s.

[0018] Preferably, step (4) comprises the following sub-steps: (a) placing the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step (3) in a hafnium-zirconium composite ceramic precursor solution and immersing it for 30 to 360 minutes to obtain a material impregnated with the hafnium-zirconium composite ceramic precursor solution; preferably, the immersion is vacuum immersion and pressure immersion; (b) curing the material impregnated with the hafnium-zirconium composite ceramic precursor solution, and then placing it in a reaction device, sealing it, evacuating the vacuum, introducing an inert gas, and cracking it at 1500 to 1800° C. for 30 to 500 minutes; preferably, the curing is curing at 150 to 350° C. for 30 to 360 minutes; (c) after the pyrolysis reaction in step (b) is completed, the temperature is lowered by program control, and after cooling to room temperature, the introduction of inert gas is stopped and the pressure is restored to atmospheric pressure; (d) repeating steps (a) to (c) at least once, preferably 1 to 10 times.

[0019] In a second aspect, the present invention provides a hafnium-based ultra-high temperature ceramic-based composite material prepared by the preparation method described in the first aspect of the present invention.

[0020] Preferably, the density of the hafnium-based ultra-high temperature ceramic-based composite material is 2.5 to 6.0 g / cm 3 and / or the thermal conductivity of the hafnium-based ultra-high temperature ceramic-based composite material at room temperature is 230 to 460 W / (m·K), and the linear ablation rate after oxyacetylene ablation at 2000°C is 1.2×10 -4 ~1.5×10 -4 mm / s, and the room temperature tensile strength is 150~255MPa.

[0021] Compared with the prior art, the present invention has at least the following beneficial effects:

[0022] (1) The present invention designs a fiber preform of a novel structure, that is, a pointed wedge-shaped preform is used as a preform for a ceramic-based composite material. The main structural feature of the pointed wedge-shaped preform in the present invention is that along a certain fiber direction, the surface of the preform gradually becomes pointed, and the geometric shape is a pointed wedge (a shape in which one end of the preform is pointed and the other end is thick). One end of the pointed wedge-shaped preform is a pointed end region, and the other end is a thick end region. The present invention finds that the use of such a pointed wedge-shaped preform can obtain a directly integrated pointed wedge-shaped ceramic-based composite material. The pointed wedge-shaped ceramic-based composite material has better structural adaptability and functionality in specific application scenarios, and the pointed wedge-shaped structure can improve the stress distribution and local strengthening effect of the material. In some applications, the pointed wedge shape helps The pointed wedge-shaped structure can effectively improve the flow state of air and liquid flow, improve energy efficiency, and better disperse the concentrated area of ​​external force, reduce crack propagation, and improve fatigue resistance under high temperature and high pressure environment, and optimize fluid flow and reduce friction resistance, especially in the fields of aerospace, power machinery, etc.; the pointed wedge-shaped structure can realize the weaving of the pointed wedge-shaped preform by mixing carbon nanotube fibers and carbon fibers, which gives full play to the high flexibility and high thermal conductivity of carbon nanotube fibers, while pure PAN-based and general asphalt-based carbon fibers cannot meet the design requirements due to their poor flexibility; and the present invention can realize the controllable adjustment of the thermal conductivity and mechanical properties of the finally prepared ceramic-based composite material by regulating the volume ratio of carbon nanotube fibers to carbon fibers in the pointed wedge-shaped preform.

[0023] (2) The present invention uses a pointed wedge-shaped preform to directly integrate and form a pointed wedge-shaped ceramic-based composite material, which can take into account both fiber continuity and cost economy, and better ensure the thermal conductivity and mechanical properties of the ceramic-based composite material. This is also something that cannot be achieved by using a ceramic-based composite material made of a conventional structural preform and then processing it into a pointed wedge-shaped product after molding. This is because the method of first molding a flat-plate-shaped ceramic-based composite material and then processing it into a product of a specific shape will cause the fibers in the tip area of ​​the product to no longer be continuous. At the same time, there is a large waste in the preparation process, which leads to high costs, and there are problems with the thermal conductivity, ablation resistance and mechanical properties of the prepared ceramic-based composite material being insufficient.

[0024] (3) The present invention uses a hafnium alkoxide and a zirconium alkoxide mixed and subjected to coordination reaction and co-hydrolysis reaction to obtain a new type of hafnium and zirconium atomic-level mixed hafnium zirconium composite ceramic precursor solution as a reactant, and prepares the hafnium-based ultra-high temperature ceramic-based composite material by precursor impregnation and cracking. The new type of hafnium zirconium composite ceramic precursor solution used can form a hafnium zirconium carbon solid solution as a ceramic matrix in the ceramic-based composite material after solidification and high-temperature cracking. The present invention finds that the hafnium zirconium carbon solid solution ceramic matrix obtained in the ceramic-based composite material has an ultra-high melting point and better ablation resistance than the mixed matrix of hafnium carbide and zirconium carbide obtained by using other hafnium zirconium ceramic precursor solutions as reactants, and can greatly improve the temperature resistance and ablation resistance of the ceramic-based composite material. In addition, the present invention can prepare a series of hafnium zirconium carbon solid solutions by using a hafnium zirconium composite ceramic precursor solution with an adjustable ratio, and after the solidification and cracking process, it is also conducive to achieving the lightweight of the ceramic-based composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of a pointed wedge-shaped preform obtained by the present invention;

[0026] Figure 2 is a schematic diagram of the pointed wedge-shaped preform obtained by the present invention at another angle;

[0027] Figure 3 This is a microstructure diagram (SEM diagram) of the hafnium-based ultrahigh temperature ceramic-based composite material obtained in Example 1 of the present invention; Figure 3 It can be seen that a hafnium-zirconium-carbon solid solution is formed in the hafnium-based ultra-high temperature ceramic matrix composite material. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] In a first aspect, the present invention provides a method for preparing a hafnium-based ultrahigh temperature ceramic-based composite material, the method comprising the following steps:

[0030] (1) Mixing carbon nanotube fibers with PAN-based carbon fibers to obtain carbon nanotube fiber / carbon fiber bidirectional cloth; in the present invention, the carbon nanotube fibers are continuous carbon nanotube fibers, and the PAN-based carbon fibers are PAN-based continuous carbon fibers; the present invention does not specifically limit the sources of the carbon nanotube fibers and the PAN-based carbon fibers, and products that can be directly purchased or synthesized by existing methods can be used; in the present invention, the carbon nanotube fibers are mixed with PAN-based carbon fibers, which is highly compatible with existing processes and can reduce costs by mixing with PAN-based carbon fibers;

[0031] (2) The carbon nanotube fiber / carbon fiber bidirectional cloth is made into a wedge-shaped preform by a lamination stitching process; in the present invention, the structure of the wedge-shaped preform can be, for example, as follows: Figure 1 and Figure 2 As shown;

[0032] (3) preparing a pyrolytic carbon interface layer on the fiber surface of the pointed wedge-shaped preform by chemical vapor deposition to obtain a pointed wedge-shaped preform having a pyrolytic carbon interface layer; the present invention does not specifically limit the process conditions of the chemical vapor deposition method, and those skilled in the art can routinely select;

[0033] (4) impregnating the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step (3) with a hafnium-zirconium composite ceramic precursor solution as an impregnation liquid, and then curing and cracking the preform, and repeating the impregnation, curing and cracking for multiple times to obtain a hafnium-based ultra-high temperature ceramic-based composite material; that is, in step (4), using the hafnium-zirconium composite ceramic precursor solution as a reactant, through a precursor impregnation and cracking process (PIP process), the hafnium-zirconium composite ceramic precursor solution is reacted with the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step (3) to prepare the hafnium-based ultra-high temperature ceramic-based composite material; the hafnium-based ultra-high temperature ceramic-based composite material obtained by the present invention is in the shape of a pointed wedge.

[0034] The present invention designs a fiber preform of a novel structure, that is, a pointed wedge-shaped preform is used as a preform for a ceramic-based composite material. The main structural feature of the pointed wedge-shaped preform in the present invention is that along a certain fiber direction, the surface of the preform gradually becomes pointed, and the geometric shape is a pointed wedge (a shape in which one end of the preform is pointed and the other end is thick). One end of the pointed wedge-shaped preform is a pointed end area, and the other end is a thick end area. The present invention finds that the use of such a pointed wedge-shaped preform can obtain a directly integrated pointed wedge-shaped ceramic-based composite material. The pointed wedge-shaped ceramic-based composite material has better structural adaptability and functionality in specific application scenarios, and the pointed wedge-shaped structure can improve the stress distribution and local strengthening effect of the material. In some applications, the pointed wedge shape is conducive to fluid flow. Dynamic optimization, reducing friction resistance, especially in the fields of aerospace, power machinery, etc., the pointed wedge structure can effectively improve the flow state of airflow and liquid flow, improve energy efficiency, and can better disperse the concentrated area of ​​external force, reduce crack propagation, and improve fatigue resistance under high temperature and high pressure environment; in addition, the present invention can realize the weaving of the pointed wedge-shaped preform through the mixed weaving of carbon nanotube fibers and carbon fibers, which gives full play to the high flexibility and high thermal conductivity of carbon nanotube fibers, while pure PAN-based and general asphalt-based carbon fibers cannot meet the design requirements due to their poor flexibility; and the present invention can realize the controllable adjustment of the thermal conductivity and mechanical properties of the finally prepared ceramic-based composite material by regulating the volume ratio of carbon nanotube fibers and PAN-based carbon fibers in the pointed wedge-shaped preform. The present invention adopts a pointed wedge-shaped preform to directly integrate and form a pointed wedge-shaped ceramic-based composite material, which can take into account both fiber continuity and cost economy, and better ensure the thermal conductivity and mechanical properties of the ceramic-based composite material. This is also something that cannot be achieved by using a ceramic-based composite material made of a conventional structural preform and then processing it into a pointed wedge-shaped product after molding. This is because the method of first molding the ceramic-based composite material and then processing it into a product of a specific shape will cause the fibers in the tip area of ​​the product to no longer be continuous. At the same time, there is a large waste in the preparation process, which leads to high costs, and there are problems with the thermal conductivity, ablation resistance and mechanical properties of the prepared ceramic-based composite material being insufficient.

[0035] According to some preferred embodiments, in step (1): the thermal conductivity of the carbon nanotube fiber is 400-1000 W / (m·K), the tensile strength is 3-5 GPa, the elongation at break is 2.5-4%, and the density is 1.4-1.5 g / cm 3; In the present invention, it is preferred to use carbon nanotube fibers with a breaking elongation of 2.5-4% and a thermal conductivity of 400-1000 W / (m·K), indicating that they have excellent flexibility and can meet the requirements of nearly 180° bending in the tip area of ​​the pointed wedge-shaped preform without breaking, thereby realizing the weaving of the pointed wedge-shaped preform, which is impossible for PAN-based carbon fibers and general mesophase asphalt-based carbon fibers; in the present invention, for example, carbon nanotube fibers purchased from the Suzhou Institute of Nano-Tech and Nano-Bionics, Chinese Academy of Sciences can be used.

[0036] According to some preferred embodiments, in the carbon nanotube fiber / carbon fiber bidirectional cloth, the carbon nanotube fibers and the PAN-based carbon fibers are vertically distributed, that is, when the carbon nanotube fiber / carbon fiber bidirectional cloth is mixed, the carbon nanotube fibers and the PAN-based carbon fibers are perpendicular to each other; and / or the surface density of the carbon nanotube fiber / carbon fiber bidirectional cloth is 300-400 g / m 2 When the carbon nanotube fiber / carbon fiber bidirectional cloth is mixed in the present invention, the ratio of carbon nanotube fiber to PAN-based carbon fiber can be adjusted to meet the subsequent weaving of a sharp wedge-shaped preform having a specific volume ratio of carbon nanotube fiber to PAN-based carbon fiber.

[0037] According to some preferred embodiments, in step (2): the lamination and stitching process is: first fold the carbon nanotube fiber / carbon fiber bidirectional cloth in a direction perpendicular to the carbon nanotube fiber, and then stack and stitch multiple (two or more) folded carbon nanotube fiber / carbon fiber bidirectional cloths to obtain a pointed wedge-shaped preform; in the present invention, when laminating, the tips of the folded carbon nanotube fiber / carbon fiber bidirectional cloths correspond to the tips, and the thick ends correspond to the thick ends, and then the stacked multiple folded carbon nanotube fiber / carbon fiber bidirectional cloths are stitched into one piece using PAN-based carbon fiber; the present invention does not make any specific limitation on the stitching method used, and those skilled in the art can make a conventional selection, for example, an orthogonal stitching method can be selected; the present invention does not make any specific limitation on the number of carbon nanotube fiber / carbon fiber bidirectional cloths used for lamination, and those skilled in the art can make a conventional selection based on the thickness requirements of the pointed wedge-shaped preform.

[0038] According to some preferred embodiments, the volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers in the pointed wedge-shaped preform is (1-3): (1-3); and / or the density of the pointed wedge-shaped preform is 0.6-0.9 g / cm 3; In the present invention, by controlling the volume ratio of the carbon nanotube fibers in the pointed wedge-shaped preform, the thermal conductivity and mechanical properties of the finally prepared ceramic-based composite material can be effectively regulated. In the present invention, preferably, the volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers in the pointed wedge-shaped preform is (1-3): (1-3), which is conducive to ensuring that the hafnium-based ultra-high temperature ceramic-based composite material with both high thermal conductivity and excellent mechanical properties is obtained; The present invention finds that if the volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers is lower than 1:3, the mechanical properties and thermal conductivity of the finally prepared ceramic-based composite material in the direction of the carbon nanotube fibers will be lower. If the volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers is higher than 3:1, the mechanical strength of the finally prepared ceramic-based composite material in the direction of the carbon fibers will be lower.

[0039] According to some preferred embodiments, in step (3): the thickness of the pyrolytic carbon interface layer is 0.1 to 2 μm; in the present invention, the thickness of the pyrolytic carbon interface layer is preferably 0.1 to 2 μm. The present invention finds that by adjusting the thickness of the pyrolytic carbon interface layer, the pore size of the preform can be controlled. When the thickness of the pyrolytic carbon interface layer is less than 0.1 μm, the internal pore size is larger, but it is easy to cause the buffer layer between the carbon nanotube fiber and the ceramic matrix to be weak, resulting in poor mechanical properties of the composite material; and when the thickness of the pyrolytic carbon interface layer is higher than 2 μm, the internal pore size is smaller, which makes it difficult to satisfy the smooth impregnation of the hafnium zirconium composite ceramic precursor solution, thereby making the filling effect of the hafnium zirconium composite ceramic precursor solution poor, and failing to effectively improve the anti-ablation performance of the composite material.

[0040] According to some preferred embodiments, in step (4): the preparation of the hafnium-zirconium composite ceramic precursor solution is: hafnium alkoxide and zirconium alkoxide are mixed evenly and subjected to coordination reaction and co-hydrolysis reaction to obtain the hafnium-zirconium composite ceramic precursor solution; in the present invention, preferably, the hafnium alkoxide is propyl hafnate (i.e., tetrapropyl hafnate), and the zirconium alkoxide is propyl zirconate (i.e., n-propyl zirconate); specifically, the preparation of the hafnium-zirconium composite ceramic precursor solution is: propyl hafnate and propyl zirconate are mixed evenly with xylene, and then ninhydrin is added as a ligand and phenolic epoxy vinyl ester resin is added and mixed evenly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C to 10°C for 100 to 150 minutes to obtain the hafnium-zirconium composite ceramic precursor solution. Zirconium composite ceramic precursor solution; the present invention does not specifically limit the phenolic epoxy vinyl ester resin, and can use directly purchased products or products synthesized by existing methods; in the present invention, the amount of the hafnium propyl ester and the zirconium propyl zirconate is such that the molar ratio of hafnium in the hafnium propyl ester to zirconium in the zirconate propyl is (0.1-99.9): (0.1-99.9); the molar amount of the ninhydrin is 0.3-0.8 times the sum of the molar amounts of the hafnium propyl ester and the zirconate propyl, preferably 0.5-0.8; the molar amount of the phenolic epoxy vinyl ester resin is 1-3 times the sum of the molar amounts of the hafnium propyl ester and the zirconate propyl, preferably 1.5-3 times; the xylene The amount of is such that the solid content of the hafnium-zirconium composite ceramic precursor solution is 40-65wt% and the viscosity is 40-120mPa·s. The present invention adopts hafnium alkoxide and zirconium alkoxide to be mixed and then subjected to coordination reaction and co-hydrolysis reaction to obtain a novel hafnium-zirconium composite ceramic precursor solution in which hafnium and zirconium are mixed at the atomic level as a reactant. In the polyhafnium zirconoxane in the hafnium-zirconium composite ceramic precursor solution, hafnium and zirconium are on the same main chain, thereby achieving atomic-level mixing. In the present invention, since hafnium and zirconium are associated elements, the properties of the two are similar, and the atomic diffusion coefficient is relatively large, so that crystal atomic replacement can be achieved. In addition, the present invention adopts ninhydrin as a ligand, which has three binding sites. Compared with the use of ligands such as acetylacetone, it can ensure that propyl hafnium and propyl zirconate The distribution of hafnium and zirconium in the main chain of the polyhafnium zirconium oxane is more uniform, so that the ratio of hafnium to zirconium in the main chain of the polyhafnium zirconium oxane is more accurate, and the excessive aggregation of a certain component is effectively avoided, resulting in a large difference in the atomic composition of the hafnium zirconium carbon solid solution in different regions. In addition, the present invention takes into account the difference in molar mass of hafnium and zirconium. By extending the reaction time in the low-temperature argon environment, it can ensure that the reaction is sufficient and uniform, and also ensure that the ratio of hafnium to zirconium in the main chain of the polyhafnium zirconium oxane is more accurate. The present invention finds that the new type of hafnium-zirconium composite ceramic precursor solution prepared by the above method, which can ensure a more accurate atomic-level mixing ratio of hafnium and zirconium in the main chain of the polyhafnium zirconium oxane, is used as an impregnation solution. After solidification and high-temperature cracking treatment, a hafnium-zirconium-carbon solid solution can be obtained in a ceramic-based composite material as a ceramic matrix.The present invention finds that the hafnium-zirconium-carbon solid solution ceramic matrix obtained in the ceramic-based composite material has an ultra-high melting point and better ablation resistance than a mixed matrix of hafnium carbide and zirconium carbide obtained by using other hafnium-zirconium ceramic precursor solutions as reactants. It can greatly improve the temperature resistance and ablation resistance of the ceramic-based composite material, and is also beneficial to improving the mechanical properties of the ceramic-based composite material.

[0041] According to some preferred embodiments, the molar ratio (atomic molar ratio) of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution is (0.1-99.9): (0.1-99.9); in the present invention, since the densities of zirconium carbide and hafnium carbide are 6.6 g / cm 3 and 12.7 g / cm 3 The density difference between the two is relatively large, so the hafnium-zirconium-carbon solid solutions with different densities can be obtained by adjusting the hafnium-zirconium atomic ratio; in some preferred embodiments of the present invention, hafnium-zirconium composite ceramic precursor solutions with different ratios of hafnium-zirconium are used as reactants, and the hafnium-zirconium composite ceramic precursor solutions are filled into the pores by vacuum and pressure impregnation, and a hafnium-based ultra-high temperature ceramic-based composite material with adjustable density is prepared by a curing and cracking process, which is also conducive to achieving lightweight ceramic-based composite materials.

[0042] According to some preferred embodiments, the solid content of the hafnium-zirconium composite ceramic precursor solution is 40-65wt% and the viscosity is 40-120mPa·s; in the present invention, the solid content is the mass percentage of the remaining part of the hafnium-zirconium composite ceramic precursor solution after solidification to the total amount of the hafnium-zirconium composite ceramic precursor solution; in the present invention, preferably, the hafnium-zirconium composite ceramic precursor solution with a solid content of 40-65wt% and a viscosity of 40-120mPa·s is used as a reactant, and a density of 2.5-6.0g / cm is prepared by repeated impregnation-curing-cracking processes. 3 Hafnium-based ultra-high temperature ceramic matrix composites.

[0043] The present invention does not specifically limit the impregnation, curing and cracking conditions used in the precursor impregnation, curing and cracking process, and those skilled in the art can make routine selections.

[0044] According to some preferred embodiments, step (4) comprises the following sub-steps:

[0045] (a) placing the pointed wedge-shaped preform with a pyrolytic carbon interface layer obtained in step (3) in a hafnium-zirconium composite ceramic precursor solution and immersing it for 30 to 360 minutes, and filling the hafnium-zirconium composite ceramic precursor solution into the pores inside the pointed wedge-shaped preform with a pyrolytic carbon interface layer to obtain a material impregnated with the hafnium-zirconium composite ceramic precursor solution; preferably, the impregnation is vacuum impregnation and pressure impregnation; the present invention does not specifically limit the process parameters of vacuum impregnation and pressure impregnation, which are well known to those skilled in the art and can be carried out using conventional parameters;

[0046] (b) curing the material impregnated with the hafnium-zirconium composite ceramic precursor solution, specifically, for example, curing can be carried out in an inert atmosphere such as argon and under heating conditions of 150-350° C., so that the hafnium-zirconium composite ceramic precursor solution inside the pores can be cross-linked and cured, and then the cured material is placed in a reaction device, sealed, evacuated, and an inert gas such as argon is introduced, the flow rate can be, for example, 100-5000 sccm, and the temperature is controlled by program control to crack at 1500-1800° C. for 30-500 min; preferably, the curing is cured at 150-350° C. for 30-360 min; in the present invention, the heating rate to 1500-1800° C. can be, for example, 0.1-10° C. / min;

[0047] (c) After the cracking reaction in step (b) is completed, the temperature is lowered by program control, and after cooling to room temperature, the introduction of inert gas is stopped, and the temperature is restored to atmospheric pressure; in the present invention, the rate of the temperature reduction can be, for example, 1 to 10° C. / minute;

[0048] (d) Repeating steps (a) to (c) at least once, preferably 1 to 10 times.

[0049] In the second aspect, the present invention provides a hafnium-based ultra-high temperature ceramic-based composite material prepared by the preparation method described in the first aspect of the present invention; the hafnium-based ultra-high temperature ceramic-based composite material prepared by the present invention has the characteristics of high thermal conductivity, high tensile strength, and excellent ablation resistance, which is manifested in a significant decrease in the line ablation rate under oxyacetylene high temperature ablation.

[0050] According to some preferred embodiments, the density of the hafnium-based ultra-high temperature ceramic-based composite material is 2.5 to 6.0 g / cm 3 and / or the thermal conductivity of the hafnium-based ultra-high temperature ceramic-based composite material at room temperature is 230 to 460 W / (m·K), and the linear ablation rate after oxyacetylene ablation at 2000°C is 1.2×10 -4 ~1.5×10 -4 mm / s, and the room temperature tensile strength is 150~255MPa.

[0051] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and deformations according to the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples, unless otherwise specified, can all be obtained from commercial channels.

[0052] Example 1

[0053] ① Provide continuous carbon nanotube fibers and PAN-based continuous carbon fibers: the continuous carbon nanotube fibers have a thermal conductivity of 600 W / (m·K), a tensile strength of 4.5 GPa, an elongation at break of 3.2%, and a density of 1.43 g / cm 3 .

[0054] ② Braided carbon nanotube fiber / carbon fiber bidirectional cloth: Continuous carbon nanotube fibers and PAN-based carbon fibers are mixed to obtain carbon nanotube fiber / carbon fiber bidirectional cloth, so that the carbon nanotube fibers and PAN-based carbon fibers are vertically distributed, and the surface density of the obtained carbon nanotube fiber / carbon fiber bidirectional cloth is 350g / m 2 .

[0055] ③ Braided pointed wedge-shaped preform: A stacking and stitching process is adopted to weave a pointed wedge-shaped preform by carbon nanotube fiber / carbon fiber bidirectional cloth, specifically: firstly, the carbon nanotube fiber / carbon fiber bidirectional cloth is folded in half along a direction perpendicular to the carbon nanotube fiber, and then a plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stacked and stitched to obtain a pointed wedge-shaped preform; when stacking, the tips of the folded carbon nanotube fiber / carbon fiber bidirectional cloths correspond to the tips, and the thick ends correspond to the thick ends, and then the stacked plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stitched into one body by using PAN-based carbon fiber; the volume ratio of carbon nanotube fiber to PAN-based carbon fiber in the obtained pointed wedge-shaped preform is 2:1, and the density of the pointed wedge-shaped preform is 0.72 g / cm 3 .

[0056] ④ Preparation of pyrolytic carbon interface layer: A pyrolytic carbon interface layer with a thickness of 0.8 μm is deposited on the fiber surface of the pointed wedge-shaped preform obtained in step ③ by chemical vapor deposition to obtain a pointed wedge-shaped preform having a pyrolytic carbon interface layer.

[0057] ⑤ Preparation of hafnium-based ultra-high temperature ceramic-based composite materials: Using a hafnium-zirconium composite ceramic precursor solution as a reactant, a pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process comprises a specific impregnation-curing-pyrolysis process as follows: placing the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step ④ in a hafnium-zirconium composite ceramic precursor solution, and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium composite ceramic The material impregnated with the precursor solution was cured in an argon atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with an argon inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 10°C / min, cooled to room temperature, the argon inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated 10 times to obtain a density of 4.8 g / cm 3 A pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material with a hafnium-zirconium-carbon solid solution as a ceramic matrix; wherein the atomic molar ratio of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution used is 80:20, the solid content of the hafnium-zirconium composite ceramic precursor solution is 59%, and the viscosity is 76 mPa·s. The hafnium-zirconium composite ceramic precursor solution used is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 80:20) in xylene, and then adding Ninhydrin as a ligand (the molar ratio of hafnium propyl ester, propyl zirconate and ninhydrin is 4:1:3) and a phenolic epoxy vinyl ester resin (the molar ratio of hafnium propyl ester, propyl zirconate and phenolic epoxy vinyl ester resin is 4:1:10) are mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C for 120 minutes to obtain the atomically uniformly mixed hafnium zirconium composite ceramic precursor solution, and the amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 59% and the viscosity is 76 mPa·s.

[0058] The room temperature thermal conductivity of the carbon nanotube fiber direction of the hafnium-based ultra-high temperature ceramic-based composite material prepared in this embodiment was measured to be 315 W / (m·K). After the oxyacetylene ablation test at 2000°C (ablation time of 500 s), the linear ablation rate was 1.2×10 - 4 mm / s, and the room temperature tensile strength of the carbon nanotube fiber direction was measured to be 196 MPa.

[0059] Example 2

[0060] ① Provide continuous carbon nanotube fibers and PAN-based continuous carbon fibers: the continuous carbon nanotube fibers have a thermal conductivity of 450 W / (m·K), a tensile strength of 4.9 GPa, an elongation at break of 3.8%, and a density of 1.43 g / cm 3 .

[0061] ② Braided carbon nanotube fiber / carbon fiber bidirectional cloth: Continuous carbon nanotube fibers and PAN-based carbon fibers are mixed to obtain carbon nanotube fiber / carbon fiber bidirectional cloth, so that the carbon nanotube fibers and PAN-based carbon fibers are vertically distributed, and the surface density of the obtained carbon nanotube fiber / carbon fiber bidirectional cloth is 350g / m 2 .

[0062] ③ Braided pointed wedge-shaped preform: A stacking and stitching process is adopted to weave a pointed wedge-shaped preform by carbon nanotube fiber / carbon fiber bidirectional cloth, specifically: firstly, the carbon nanotube fiber / carbon fiber bidirectional cloth is folded in half along a direction perpendicular to the carbon nanotube fiber, and then a plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stacked and stitched to obtain a pointed wedge-shaped preform; when stacking, the tips of the folded carbon nanotube fiber / carbon fiber bidirectional cloths correspond to the tips, and the thick ends correspond to the thick ends, and then the stacked plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stitched into one body by using PAN-based carbon fiber; the volume ratio of carbon nanotube fiber to PAN-based carbon fiber in the obtained pointed wedge-shaped preform is 2:1, and the density of the pointed wedge-shaped preform is 0.72 g / cm 3 .

[0063] ④ Preparation of pyrolytic carbon interface layer: A pyrolytic carbon interface layer with a thickness of 0.8 μm is deposited on the fiber surface of the pointed wedge-shaped preform obtained in step ③ by chemical vapor deposition to obtain a pointed wedge-shaped preform having a pyrolytic carbon interface layer.

[0064] ⑤ Preparation of hafnium-based ultra-high temperature ceramic-based composite materials: Using a hafnium-zirconium composite ceramic precursor solution as a reactant, a pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process comprises a specific impregnation-curing-pyrolysis process as follows: placing the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step ④ in a hafnium-zirconium composite ceramic precursor solution, and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium composite ceramic The material impregnated with the precursor solution was cured in an argon atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with an argon inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 10°C / min, cooled to room temperature, the argon inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated 10 times to obtain a density of 4.8 g / cm 3 A hafnium-based ultra-high temperature ceramic-based composite material; wherein, in the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 80:20, the solid content of the hafnium-zirconium composite ceramic precursor solution is 59%, and the viscosity is 76 mPa·s. The hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 80:20) in xylene, and then adding ninhydrin as a ligand ( Propyl hafnium ester, propyl zirconate and ninhydrin (the molar ratio of hafnium ester, propyl zirconate and ninhydrin is 4:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium ester, propyl zirconate and phenolic epoxy vinyl ester resin is 4:1:10) are mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C for 120 minutes to obtain the atomically uniformly mixed hafnium zirconium composite ceramic precursor solution, and the amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 59% and the viscosity is 76 mPa·s.

[0065] The room temperature thermal conductivity of the carbon nanotube fiber direction of the hafnium-based ultra-high temperature ceramic-based composite material prepared in this embodiment was measured to be 241 W / (m·K). After the oxyacetylene ablation test at 2000°C (ablation time was 500s), the linear ablation rate was 1.2×10 - 4 mm / s, and the room temperature tensile strength of the carbon nanotube fiber direction was measured to be 213 MPa.

[0066] Example 3

[0067] ① Provide continuous carbon nanotube fibers and PAN-based continuous carbon fibers: the continuous carbon nanotube fibers have a thermal conductivity of 800 W / (m·K), a tensile strength of 4.0 GPa, an elongation at break of 2.8%, and a density of 1.43 g / cm 3 .

[0068] ② Braided carbon nanotube fiber / carbon fiber bidirectional cloth: Continuous carbon nanotube fibers and PAN-based carbon fibers are mixed to obtain carbon nanotube fiber / carbon fiber bidirectional cloth, so that the carbon nanotube fibers and PAN-based carbon fibers are vertically distributed, and the surface density of the obtained carbon nanotube fiber / carbon fiber bidirectional cloth is 350g / m 2 .

[0069] ③ Braided pointed wedge-shaped preform: A stacking and stitching process is adopted to weave a pointed wedge-shaped preform by carbon nanotube fiber / carbon fiber bidirectional cloth, specifically: firstly, the carbon nanotube fiber / carbon fiber bidirectional cloth is folded in half along a direction perpendicular to the carbon nanotube fiber, and then a plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stacked and stitched to obtain a pointed wedge-shaped preform; when stacking, the tips of the folded carbon nanotube fiber / carbon fiber bidirectional cloths correspond to the tips, and the thick ends correspond to the thick ends, and then the stacked plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stitched into one body by using PAN-based carbon fiber; the volume ratio of carbon nanotube fiber to PAN-based carbon fiber in the obtained pointed wedge-shaped preform is 2:1, and the density of the pointed wedge-shaped preform is 0.72 g / cm 3 .

[0070] ④ Preparation of pyrolytic carbon interface layer: A pyrolytic carbon interface layer with a thickness of 0.8 μm is deposited on the fiber surface of the pointed wedge-shaped preform obtained in step ③ by chemical vapor deposition to obtain a pointed wedge-shaped preform having a pyrolytic carbon interface layer.

[0071] ⑤ Preparation of hafnium-based ultra-high temperature ceramic-based composite materials: Using a hafnium-zirconium composite ceramic precursor solution as a reactant, a pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process comprises a specific impregnation-curing-pyrolysis process as follows: placing the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step ④ in a hafnium-zirconium composite ceramic precursor solution, and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium composite ceramic The material impregnated with the precursor solution was cured in an argon atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with an argon inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 10°C / min, cooled to room temperature, the argon inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated 10 times to obtain a density of 4.8 g / cm 3 A hafnium-based ultra-high temperature ceramic-based composite material; wherein, in the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 80:20, the solid content of the hafnium-zirconium composite ceramic precursor solution is 59%, and the viscosity is 76 mPa·s. The hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 80:20) in xylene, and then adding ninhydrin as a ligand ( Propyl hafnium ester, propyl zirconate and ninhydrin (the molar ratio of hafnium ester, propyl zirconate and ninhydrin is 4:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium ester, propyl zirconate and phenolic epoxy vinyl ester resin is 4:1:10) are mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C for 120 minutes to obtain the atomically uniformly mixed hafnium zirconium composite ceramic precursor solution, and the amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 59% and the viscosity is 76 mPa·s.

[0072] The room temperature thermal conductivity of the carbon nanotube fiber direction of the hafnium-based ultra-high temperature ceramic-based composite material prepared in this embodiment was measured to be 403 W / (m·K). After the oxyacetylene ablation test at 2000°C (ablation time was 500 s), the linear ablation rate was 1.2×10 - 4 mm / s, and the room temperature tensile strength of the carbon nanotube fiber direction was measured to be 173 MPa.

[0073] Example 4

[0074] ① Provide continuous carbon nanotube fibers and PAN-based continuous carbon fibers: the continuous carbon nanotube fibers have a thermal conductivity of 600 W / (m·K), a tensile strength of 4.5 GPa, an elongation at break of 3.2%, and a density of 1.43 g / cm 3 .

[0075] ② Braided carbon nanotube fiber / carbon fiber bidirectional cloth: Continuous carbon nanotube fibers and PAN-based carbon fibers are mixed to obtain carbon nanotube fiber / carbon fiber bidirectional cloth, so that the carbon nanotube fibers and PAN-based carbon fibers are vertically distributed, and the surface density of the obtained carbon nanotube fiber / carbon fiber bidirectional cloth is 324g / m 2 .

[0076] ③ Braided pointed wedge-shaped preform: A stacking and stitching process is adopted to weave a pointed wedge-shaped preform through carbon nanotube fiber / carbon fiber bidirectional cloth, specifically: firstly, the carbon nanotube fiber / carbon fiber bidirectional cloth is folded in half along a direction perpendicular to the carbon nanotube fiber, and then a plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stacked and stitched to obtain a pointed wedge-shaped preform; when stacking, the tips of the folded carbon nanotube fiber / carbon fiber bidirectional cloths correspond to the tips, and the thick ends correspond to the thick ends, and then the stacked plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stitched into one body by using PAN-based carbon fiber; the volume ratio of carbon nanotube fiber to PAN-based carbon fiber in the obtained pointed wedge-shaped preform is 3:1, and the density of the pointed wedge-shaped preform is 0.68 g / cm 3 .

[0077] ④ Preparation of pyrolytic carbon interface layer: A pyrolytic carbon interface layer with a thickness of 0.8 μm is deposited on the fiber surface of the pointed wedge-shaped preform obtained in step ③ by chemical vapor deposition to obtain a pointed wedge-shaped preform having a pyrolytic carbon interface layer.

[0078] ⑤ Preparation of hafnium-based ultra-high temperature ceramic-based composite materials: Using a hafnium-zirconium composite ceramic precursor solution as a reactant, a pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process comprises a specific impregnation-curing-pyrolysis process as follows: placing the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step ④ in a hafnium-zirconium composite ceramic precursor solution, and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the hafnium-zirconium composite ceramic precursor solution, wherein the vacuum impregnation pressure is 200 Pa, and the pressurized impregnation pressure is 1.5 MPa; then the obtained hafnium-zirconium composite ceramic The material impregnated with the precursor solution was cured in an argon atmosphere at a curing temperature of 260°C, a curing time of 120 min at 260°C, and a heating rate of 5°C / min to 260°C. The cured material was then placed in a reaction device, sealed, evacuated, and introduced with an argon inert gas at a flow rate of 1000 sccm. The temperature was set to be controlled by a program at a heating rate of 5°C / min, and the material was pyrolyzed at 1600°C for 240 min. After the pyrolysis reaction was completed, the temperature was lowered at a rate of 10°C / min, cooled to room temperature, the argon inert gas was turned off, and the material was restored to atmospheric pressure. The immersion-curing-pyrolysis process was repeated 10 times to obtain a density of 4.7 g / cm 3 A hafnium-based ultra-high temperature ceramic-based composite material; wherein, in the hafnium-zirconium composite ceramic precursor solution, the atomic molar ratio of hafnium to zirconium is 80:20, the solid content of the hafnium-zirconium composite ceramic precursor solution is 59%, and the viscosity is 76 mPa·s. The hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing propyl hafnium and propyl zirconate (in an amount such that the molar ratio of hafnium in propyl hafnium and zirconium in propyl zirconate is 80:20) in xylene, and then adding ninhydrin as a ligand ( Propyl hafnium ester, propyl zirconate and ninhydrin (the molar ratio of hafnium ester, propyl zirconate and ninhydrin is 4:1:3) and phenolic epoxy vinyl ester resin (the molar ratio of hafnium ester, propyl zirconate and phenolic epoxy vinyl ester resin is 4:1:10) are mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 5°C for 120 minutes to obtain the atomically uniformly mixed hafnium zirconium composite ceramic precursor solution, and the amount of xylene used is such that the solid content of the hafnium zirconium composite ceramic precursor solution is 59% and the viscosity is 76 mPa·s.

[0079] The room temperature thermal conductivity of the carbon nanotube fiber direction of the hafnium-based ultra-high temperature ceramic-based composite material prepared in this embodiment was measured to be 368 W / (m·K). After the oxyacetylene ablation test at 2000°C (ablation time was 500s), the linear ablation rate was 1.2×10 - 4 mm / s, and the room temperature tensile strength of the carbon nanotube fiber direction was measured to be 221 MPa.

[0080] It can be seen from the above examples 1 to 4 that, compared with example 1, the thermal conductivity of the carbon nanotube fiber selected in example 2 is reduced from 600W / m·K to 450W / m·K, and the tensile strength and elongation at break also change accordingly. Other conditions remain unchanged, so that the thermal conductivity of the hafnium-based ultra-high temperature ceramic-based composite material finally prepared is reduced from 315W / m·K to 241W / m·K, and the tensile strength of the hafnium-based ultra-high temperature ceramic-based composite material is increased from 196MPa to 213MPa. Compared with example 1, the thermal conductivity of the carbon nanotube fiber selected in example 3 is increased from 600W / m·K to 800W / m·K, and the tensile strength and elongation at break also change accordingly. Other conditions remain unchanged, so that the thermal conductivity of the hafnium-based ultra-high temperature ceramic-based composite material finally prepared is increased from 315W / m·K to 403W / m·K, and the tensile strength of the hafnium-based ultra-high temperature ceramic-based composite material is reduced from 196MPa to 173MPa. Compared with Example 1, the surface density of the carbon nanotube fiber / carbon fiber bidirectional fabric of Example 4 is 350 g / m 2 Reduced to 324g / m 2 The volume ratio of carbon nanotube fiber to PAN-based carbon fiber was increased from 2:1 to 3:1. Since the density of carbon nanotube fiber is lower than that of carbon fiber, the density of the wedge-shaped preform was increased from 0.72 g / cm 3 Reduced to 0.68g / cm 3 The increase in the volume content of carbon nanotube fibers will also increase the tensile strength in this direction, so that the thermal conductivity of the finally prepared hafnium-based ultra-high temperature ceramic-based composite material is increased from 315W / m·K to 368W / m·K, and the tensile strength of the hafnium-based ultra-high temperature ceramic-based composite material is increased from 196MPa to 221MPa.

[0081] Embodiments 5 to 11

[0082] Examples 5 to 11 are basically the same as Example 1. The specific process parameters and the properties of the hafnium-based ultra-high temperature ceramic-based composite materials finally prepared are shown in Table 1 below. The other preparation processes are the same as those in Example 1.

[0083] Table 1

[0084]

[0085]

[0086] From the results in Table 1, it can be seen that compared with Example 1, the surface density of the carbon nanotube fiber / carbon fiber bidirectional fabric of Example 6 is increased from 350 g / m 2 Increased to 412g / m 2 The volume ratio of carbon nanotube fiber to carbon fiber is reduced from 2:1 to 1:5. Since the density of carbon nanotube fiber is lower than that of PAN-based carbon fiber, the density of the preform is reduced from 0.72 g / cm3 Increased to 0.93g / cm 3 The reduction in the volume content of carbon nanotube fibers will also affect the tensile strength in this direction, resulting in the thermal conductivity of the final hafnium-based ultra-high temperature ceramic-based composite material being reduced from 315W / m·K to 103W / m·K, and the tensile strength of the hafnium-based ultra-high temperature ceramic-based composite material being reduced from 196MPa to 132MPa. Compared with Example 1, the thickness of the fiber interface layer of Example 9 is increased from 0.8μm to 3μm, resulting in a significant reduction in the internal pore size, which reduces the volume content of the subsequent hafnium-zirconium-carbon solid solution, and ultimately results in the density of the hafnium-based ultra-high temperature ceramic-based composite material being increased from 4.8g / cm 3 Reduced to 3.5g / cm 3 At the same time, the oxyacetylene line ablation rate increased from 1.2×10 - 4 mm / s increased to 2.5×10 -4 mm / s. As the thickness of the interface layer increases, the mechanical properties are improved, so that the tensile strength of the hafnium-based ultra-high temperature ceramic matrix composite material is increased from 196MPa to 268MPa. Compared with Example 1, the thickness of the fiber interface layer of Example 10 is reduced from 0.8μm to 0.05μm, resulting in an increase in the internal pore size, which increases the volume content of the subsequent hafnium-zirconium-carbon solid solution, and ultimately leads to the density of the hafnium-based ultra-high temperature ceramic matrix composite material from 4.8g / cm 3 Increased to 5.5g / cm 3 At the same time, the oxyacetylene line ablation rate increased from 1.2×10 -4 mm / s decreased to 0.95×10 -4 mm / s. As the thickness of the interface layer decreases, the mechanical properties are affected, causing the tensile strength of the composite material to decrease from 196MPa to 108MPa.

[0087] Comparative Example 1

[0088] ①Same as step ① of Example 1.

[0089] ②Same as step ② of Example 1.

[0090] ③ Braided flat preform: A flat fiber preform is obtained by weaving carbon nanotube fiber / carbon fiber bidirectional cloth using a lamination and stitching process. Specifically, multiple carbon nanotube fiber / carbon fiber bidirectional cloths are stacked and stitched together. The volume ratio of carbon nanotube fiber to PAN-based carbon fiber in the obtained flat preform is 2:1, and the density of the flat preform is 0.72g / cm 3 ; The flat plate preform obtained in step ③ is used to replace the pointed wedge-shaped preform in Example 1 to carry out the same subsequent steps ④ and ⑤ as in Example 1.

[0091] The room temperature thermal conductivity of the carbon nanotube fiber direction of the flat-plate hafnium-based ultra-high temperature ceramic-based composite material prepared in this comparative example is measured to be 318 W / m·K. After the oxyacetylene ablation test at 2000°C (ablation time is 500 s), the linear ablation rate is 1.2×10 -4 mm / s, and the room temperature tensile strength of the carbon nanotube fiber direction was measured to be 198 MPa.

[0092] In this comparative example, the prepared flat plate-shaped hafnium-based ultra-high temperature ceramic-based composite material is machined into a pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material, and the room temperature thermal conductivity of the prepared pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material in the carbon nanotube fiber direction is measured to be 188 W / m·K. After the oxyacetylene 2000°C ablation test (ablation time is 500s), the linear ablation rate is 1.8×10 -4 mm / s, and the room temperature tensile strength of the carbon nanotube fiber direction was measured to be 142 MPa.

[0093] Although the performance of the flat-plate hafnium-based ultra-high temperature ceramic-based composite material prepared in this comparative example is basically the same as that of the pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material prepared in Example 1, when the flat-plate hafnium-based ultra-high temperature ceramic-based composite material prepared in this comparative example is processed into a pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material by traditional machining, this traditional method will cause the fibers in the tip area of ​​the product to no longer be continuous, resulting in a significant decrease in the thermal conductivity, ablation resistance and mechanical properties of the pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material.

[0094] Comparative Example 2

[0095] ①Same as step ① of Example 1.

[0096] ②Same as step ② of Example 1.

[0097] ③ is the same as step ③ of Example 1.

[0098] ④ is the same as step ④ of Example 1.

[0099] ⑤ Preparation of hafnium-based ultra-high temperature ceramic-based composite materials: Using a molecularly uniformly mixed hafnium-zirconium ceramic precursor solution as a reactant, a hafnium-based ultra-high temperature ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process comprises a specific impregnation-curing-pyrolysis process as follows: placing the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step ④ in a hafnium-zirconium ceramic precursor solution, and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a material impregnated with the hafnium-zirconium ceramic precursor solution, wherein the vacuum impregnation pressure is 2 00Pa, the pressure of the pressurized impregnation is 1.5MPa; then the material impregnated with the obtained hafnium zirconium ceramic precursor solution is cured in an argon atmosphere, the curing temperature is 260°C, the curing time at 260°C is 120min, the rate of heating to 260°C is 5°C / min, and then the cured material is placed in a reaction device, sealed, evacuated, and argon inert gas is introduced at a flow rate of 1000sccm, the program is set to control the temperature, the heating rate is 5°C / min, and the pyrolysis is performed at 1600°C for 240min, and the pyrolysis reaction result is After the beam is formed, the temperature is cooled at a rate of 10°C / min, cooled to room temperature, the argon inert gas is turned off, and the pressure is restored to atmospheric pressure; the impregnation-solidification-cracking process is repeated 10 times to obtain a wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material with hafnium carbide and zirconium carbide as a ceramic matrix; wherein the atomic molar ratio of hafnium to zirconium in the hafnium-zirconium ceramic precursor solution used is 80:20, and the solid content of the hafnium-zirconium ceramic precursor solution is 59%; wherein the hafnium-zirconium ceramic precursor solution is prepared by: mixing propyl hafnate and propyl zirconate (in an amount such that the hafnium ester in the The molar ratio of hafnium to zirconium of zirconate is 80:20) is uniformly mixed in xylene, and then acetylacetone is added as a ligand (the molar ratio of hafnium propyl ester, zirconate propyl ester and acetylacetone is 4:1:3) and allyl phenolic resin (the molar ratio of hafnium propyl ester, zirconate propyl ester and allyl phenolic resin is 4:1:10) and mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 15° C. for 70 minutes to obtain a hafnium zirconium ceramic precursor solution, and the amount of xylene used is such that the solid content of the hafnium zirconium ceramic precursor solution is 59%.

[0100] The room temperature thermal conductivity of the carbon nanotube fiber direction of the pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material prepared in this comparative example is measured to be 315 W / m·K. After the oxyacetylene ablation test at 2000°C (ablation time is 500s), the linear ablation rate is 1.7×10 -4 mm / s, and the room temperature tensile strength of the carbon nanotube fiber direction was measured to be 185 MPa.

[0101] Comparative Example 3

[0102] ①Same as step ① of Example 1.

[0103] ②Same as step ② of Example 1.

[0104] ③ is the same as step ③ of Example 1.

[0105] ④ is the same as step ④ of Example 1.

[0106] ⑤ Preparation of hafnium-based ultra-high temperature ceramic-based composite materials: Using a molecular-level uniformly mixed hafnium-zirconium ceramic precursor solution as a reactant, a hafnium-based ultra-high temperature ceramic-based composite material is prepared by a precursor impregnation and pyrolysis process, wherein the precursor impregnation and pyrolysis process comprises a specific impregnation-curing-pyrolysis process as follows: placing the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step ④ in a hafnium-zirconium ceramic precursor solution, and sequentially performing vacuum impregnation for 60 minutes and pressurized impregnation for 60 minutes to obtain a hafnium-zirconium ceramic precursor impregnated material, wherein the vacuum impregnation pressure is 200Pa, the pressure of the pressurized impregnation is 1.5MPa; then the obtained hafnium zirconium ceramic precursor impregnated material is cured in an argon atmosphere, the curing temperature is 260°C, the curing time at 260°C is 120min, the rate of heating to 260°C is 5°C / min, and then the cured material is placed in a reaction device, sealed, evacuated, argon inert gas is introduced, the flow rate is 1000sccm, the program is set to control the temperature, the heating rate is 5°C / min, and the pyrolysis is performed at 1600°C for 240min, and the pyrolysis reaction After the reaction is completed, the temperature is cooled at a rate of 10°C / min, cooled to room temperature, the argon inert gas is turned off, and the pressure is restored to atmospheric pressure; the impregnation-curing-cracking process is repeated 10 times to obtain a wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material with hafnium carbide and zirconium carbide as a ceramic matrix; wherein the hafnium-zirconium ceramic precursor solution used has a molar ratio of hafnium to zirconium of 80:20, and the solid content of the hafnium-zirconium ceramic precursor is 59%; wherein the hafnium-zirconium ceramic precursor solution is prepared by: mixing polyhafnium oxide and polyzirconium oxide (in an amount such that polyhafnium oxide The hafnium in the polyzirconium is 80:20 in molar ratio and the zirconium in the polyzirconium oxane is 80:20) and allyl phenolic resin (the molar ratio of polyhafnium oxane, polyzirconium oxane and allyl phenolic resin is 4:1:10) are mixed uniformly to obtain a mixed solution, and the mixed solution is reacted in an argon atmosphere at 15° C. for 70 minutes to obtain a hafnium zirconium ceramic precursor uniformly mixed at the molecular level, and then xylene is added to the hafnium zirconium ceramic precursor and mixed uniformly to obtain a hafnium zirconium ceramic precursor solution, and the solid content of the hafnium zirconium ceramic precursor solution is adjusted to 59% by adjusting the amount of xylene.

[0107] The room temperature thermal conductivity of the carbon nanotube fiber direction of the pointed wedge-shaped hafnium-based ultra-high temperature ceramic-based composite material prepared in this comparative example is measured to be 315 W / m·K. After the oxyacetylene ablation test at 2000°C (ablation time is 500 s), the linear ablation rate is 2.1×10 -4 mm / s, and the room temperature tensile strength of the carbon nanotube fiber direction was measured to be 178 MPa.

[0108] It can be seen from the comparison between Example 1 and Comparative Examples 2 to 3 that by using the hafnium-zirconium composite ceramic precursor solution of the present invention as an impregnation solution, a hafnium-zirconium-carbon solid solution ceramic matrix can be obtained in the ceramic-based composite material, which is beneficial to improving the ablation resistance and mechanical properties of the ceramic-based composite material.

[0109] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a hafnium-based ultra-high temperature ceramic-based composite material, characterized in that: The method comprises the following steps: (1) mixing carbon nanotube fibers with PAN-based carbon fibers to obtain carbon nanotube fiber / carbon fiber bidirectional fabric; (2) using a lamination stitching process to make a carbon nanotube fiber / carbon fiber bidirectional cloth into a wedge-shaped preform; (3) preparing a pyrolytic carbon interface layer on the fiber surface of the pointed wedge-shaped preform by chemical vapor deposition to obtain a pointed wedge-shaped preform having a pyrolytic carbon interface layer; (4) impregnating the wedge-shaped preform having a pyrolytic carbon interface layer obtained in step (3) with a hafnium-zirconium composite ceramic precursor solution as an impregnation liquid, then curing and cracking the preform, and repeating the impregnation, curing and cracking multiple times to obtain a hafnium-based ultrahigh temperature ceramic-based composite material.

2. The preparation method according to claim 1, characterized in that: In step (1): The carbon nanotube fiber has a thermal conductivity of 400 to 1000 W / (m·K), a tensile strength of 3 to 5 GPa, and an elongation at break of 2.5 to 4%. In the carbon nanotube fiber / carbon fiber bidirectional fabric, the carbon nanotube fibers and the PAN-based carbon fibers are vertically distributed; and / or The surface density of the carbon nanotube fiber / carbon fiber bidirectional cloth is 300-400 g / m 2 .

3. The preparation method according to claim 1, characterized in that: In step (2): The lamination and stitching process is as follows: firstly, the carbon nanotube fiber / carbon fiber bidirectional cloth is folded in half along a direction perpendicular to the carbon nanotube fiber, and then a plurality of folded carbon nanotube fiber / carbon fiber bidirectional cloths are stacked and stitched to obtain a pointed wedge-shaped preform.

4. The preparation method according to claim 1, characterized in that: The volume ratio of the carbon nanotube fibers to the PAN-based carbon fibers in the pointed wedge-shaped preform is (1-3): (1-3); and / or The density of the pointed wedge-shaped preform is 0.6-0.9 g / cm 3 .

5. The preparation method according to claim 1, characterized in that: In step (3): The thickness of the pyrolytic carbon interface layer is 0.1-2 μm.

6. The preparation method according to claim 1, characterized in that: In step (4): The hafnium-zirconium composite ceramic precursor solution is prepared by uniformly mixing hafnium alkoxide and zirconium alkoxide and subjecting them to coordination reaction and co-hydrolysis reaction to obtain the hafnium-zirconium composite ceramic precursor solution; and / or The molar ratio of hafnium to zirconium in the hafnium-zirconium composite ceramic precursor solution is (0.1-99.9): (0.1-99.9).

7. The preparation method according to claim 1, characterized in that: The hafnium-zirconium composite ceramic precursor solution has a solid content of 40-65wt% and a viscosity of 40-120mPa·s.

8. The preparation method according to claim 1, characterized in that: Step (4) includes the following sub-steps: (a) placing the pointed wedge-shaped preform having a pyrolytic carbon interface layer obtained in step (3) in a hafnium-zirconium composite ceramic precursor solution and immersing it for 30 to 360 minutes to obtain a material impregnated with the hafnium-zirconium composite ceramic precursor solution; preferably, the immersion is vacuum immersion and pressure immersion; (b) curing the material impregnated with the hafnium-zirconium composite ceramic precursor solution, and then placing it in a reaction device, sealing it, evacuating it, introducing an inert gas, and cracking it at 1500-1800° C. for 30-500 min; preferably, the curing is performed at 150-350° C. for 30-360 min; (c) after the cracking reaction in step (b) is completed, the temperature is lowered by program control, and after cooling to room temperature, the introduction of inert gas is stopped, and the pressure is restored to atmospheric pressure; (d) Repeating steps (a) to (c) at least once, preferably 1 to 10 times.

9. A hafnium-based ultrahigh temperature ceramic-based composite material prepared by the preparation method according to any one of claims 1 to 8.

10. The hafnium-based ultra-high temperature ceramic-based composite material according to claim 9, characterized in that: The density of the hafnium-based ultra-high temperature ceramic-based composite material is 2.5 to 6.0 g / cm 3 ; and / or The hafnium-based ultra-high temperature ceramic-based composite material has a thermal conductivity of 230 to 460 W / (m·K) at room temperature, and a linear ablation rate of 1.2×10 -4 ~1.5×10 -4 mm / s, and the room temperature tensile strength is 150~255MPa.

Citation Information

Patent Citations

  • Heat transmission ceramic matrix composite material and preparation method thereof

    CN109320278A

  • Extremely-high-temperature anti-ablation heat conduction composite material and preparation method thereof

    CN113563091A

  • Heat-conducting ceramic-based composite material with profiling structure and preparation method of heat-conducting ceramic-based composite material

    CN117263705A

  • Carbon fiber composite material, and brake member, structural member for semiconductor, heat resistant panel and heat sink using the carbon fiber composite material

    US20150005151A1

  • Polymer-derived ceramic reinforced with boron nitride

    US20220324760A1